Carotid intima-media thickness in patients with mild or moderate psoriasis - Bańska-Kisiel, Katarzyna; Haberka, Maciej; Bergler-Czop, Beata; Brzezińska-Wcisło, Ligia; Okopień, Bogusław; Gąsior, Zbigniew (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2016)
Introduction : Psoriasis is a chronic inflammatory disease associated with a significantly higher morbidity and various comorbidities (obesity, metabolic syndrome, diabetes). Previous studies focused mainly on patients with severe psoriasis who were found to have increased markers of early atherosclerosis, higher intima-media thickness (IMT) values. Aim : To evaluate the association between the severity or duration of psoriasis and carotid IMT in patients with mild and moderate psoriasis. Material and methods : We studied seventy four patients with mild and moderate psoriasis. Clinical assessment and common carotid artery (CCA) IMT measurements were performed in all patients. Results : The mean CCA IMT value was 1.03 ±0.37 mm, mean PASI score (psoriasis area severity index) was 18.6 ±10.5. There was a significant association between PASI score and IMT values (r = 0.33; p = 0.007) adjusted for age, psoriasis duration, blood pressure and smoking. However, we found no correlations between carotid IMT and disease duration or other clinical variables. Conclusions : The severity of psoriasis is associated with carotid IMT even in patients with mild and moderate psoriasis.